2008
DOI: 10.1258/rsmmsl.48.2.163
|View full text |Cite
|
Sign up to set email alerts
|

Determination of age from pubic symphysis: an autopsy study

Abstract: The present study was conducted on three hundred and thirty-six cases brought for autopsy to the Department of Forensic Medicine, Government Medical College, Amritsar, Punjab, India, during the period 2000-2002. Pubic bones of either sex were analysed according to Todd's method (1920; 1921a,b,c) as modified by McKern and Stewart (1957) to assess and compare the known age of the corpses. Cases belonged to both sexes, i.e. 79.46% males and 20.54% females. All the cases were above the age of 17 years. No differen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 7 publications
(21 reference statements)
0
12
0
Order By: Relevance
“…The study of the pelvis in cadavers has long been used for forensic purposes [9][10][11][12][13][14][15][16][17][18][19][20]. In the living, the analysis of the process of ossification and fusion of pelvic bones has mainly focused on the iliac crest.…”
Section: Introductionmentioning
confidence: 99%
“…The study of the pelvis in cadavers has long been used for forensic purposes [9][10][11][12][13][14][15][16][17][18][19][20]. In the living, the analysis of the process of ossification and fusion of pelvic bones has mainly focused on the iliac crest.…”
Section: Introductionmentioning
confidence: 99%
“…The results obtained from the present study were compared to McKern and Stewart study and other similar researches. [8][9][10][11][12] The findings of the present study are compared with those of McKern and Stewart study as shown in Table 2.…”
Section: Discussionmentioning
confidence: 99%
“…Thus the likelihood of changes in each component being more pronounced in early stages are high compared to the older age group. 9 The results of the current research were also compared to similar research in Punjab 10 and the results are drafted in Table 3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar Indian studies have also been conducted on pubic bones. 14,15,23 Observations made in Western countries are not applicable to Indian populations due to racial differences. Also bony changes depend on climate, nutrition, geographical region, races, etc., so no universal standard can be devised for estimation of age.…”
Section: Introductionmentioning
confidence: 99%